UPM rises in varsities ranking - Aziz, Hazlina (New Straits Times, 2016)
THREE Malaysian universities made it to the top 100 in the recent results of Times Higher Education (THE) 2017 BRICS & Emerging Economies University Rankings. Ledby Universiti Putra Malaysia (UPM) in joint 89th place, the other two universities are Universiti Teknologi Petronas (UTP) and Universiti Teknologi Malaysia (UTM).